Comparative phytochemical, antioxidant, and antibacterial study of different parts of Doigota plants (Bixa orellana L.) - Ahmed, Sium (2021)
Phytochemical screening indicated the presence of nine different phytochemicals in varying degrees, which suggests the chemical diversity of this plant. Quantification of phenolics, flavonoids, and tannins was performed where leaf extracts contained significantly higher quantities of these phytochemicals than extracts from seed and branch. The highest phenolics (186.02 mg/g) were found in the methanolic extract of the leaf, whereas the highest flavonoids (61.01 mg/g) and tannins (36.74 mg/g) were found in aqueous extract of the leaf. Antioxidant activity has been evaluated by DPPH scavenging assay where the aqueous extract of leaf showed 93.62% scavenging activity at 800 μg/mL extract concentration. Although the extracts prevented the growth of both Gram-positive and Gram-negative bacteria, the antibacterial activity (zone of inhibition) of aqueous and methanolic extracts of the leaves were higher than those of the seed and branch extracts against Gram-negative (Escherichia coli) and Gram-positive (Bacillus subtilis) bacteria, respectively.